CHANGES IN THE PHOSPHOLIPID CONTENTS OF NUCLEAR MEMBRANE AND CHROMATIN OF GERMINATING CEREAL SEEDS UNDER INFLUENCE OF DIFFERENT FACTORS (Proceedings of the YSU B: Chemical and Biological Sciences, 2006)
The contents of chromatin phospholipid and nuclear membrane of germination cereal seeds have been investigated. It is shown, that the investigated nuclear sub fractions of cereal seedlings – nuclear membrane and chromatin differ in content and composition of phospholipids. At treatment of seeds with gibberellin (GA3) has occurred the redistribution of phospholipids in content and composition. It is shown that specimens of nuclear membranes and chromatin of germinating cereal seeds differ both in content and composition of phospholipids. In studied nuclear sub fractions the sensibility to influence of factors of different nature show different classes of phospholipids.
Keywords: cereal seeds; chromatin phospholipid; nuclear membrane; composition of phospholipids